A Case for Place as a Mediating Artifact in Transnational Learning Contexts: A Cultural Historial Place-Based Inquiry - Kimeka Campbell (Adult Education Research Conference, 2015)
To provide appropriate learner-centered contexts for transnational adult learners in the United States, the central place-based knowledge perspectives that learners possess upon arrival must be preserved. This paper discusses using the cultural historical activity theory to underscore place as a mediating instrument in the preservation process.
Keywords: place pedagogy; neighborhood learning; cultural historical activity theory